2018
DOI: 10.4209/aaqr.2016.12.0581
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fog in Urban Heat Island Modification in Kraków, Poland

Abstract: The impact of fog on relief modified urban heat island (RMUHI) in Kraków has been presented using fog observations at 06 UTC from two meteorological stations: a rural one (Balice, B) and an urban one (Botanical Garden, BG) from the period 2006-2015. Daily UHI magnitude for the valley floor for the same period was estimated as T min BG-T min B, while for the period 2010-2015, eight daily courses of UHI were available, for the urban areas in the valley floor and 50 m above it, together with air temperature inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The location of the city of Krakow in the Vistula River valley determines certain features of its natural climate, including the formation of cold air pools, frequent temperature inversions, and increased frequency of freezing temperatures, calm or light wind, and fog. These circumstances favour the accumulation of pollutants near the ground and the formation of smog, causing values to exceed the acceptable and target levels [31,43,[52][53][54][55][56][57][58]. This explains the substantial differences in the PM 2.5 concentrations between calendar seasons (spring, summer, autumn, and winter).…”
Section: Pca Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The location of the city of Krakow in the Vistula River valley determines certain features of its natural climate, including the formation of cold air pools, frequent temperature inversions, and increased frequency of freezing temperatures, calm or light wind, and fog. These circumstances favour the accumulation of pollutants near the ground and the formation of smog, causing values to exceed the acceptable and target levels [31,43,[52][53][54][55][56][57][58]. This explains the substantial differences in the PM 2.5 concentrations between calendar seasons (spring, summer, autumn, and winter).…”
Section: Pca Analysismentioning
confidence: 99%
“…Air pollution levels are influenced not only by current emissions associated with the municipal and housing sector, transport, and industry, but also by meteorological conditions (air temperature, precipitation, and wind speed) and the type of atmospheric circulation [25][26][27][28][29][30]. Atmospheric circulation is one of the most important factors determining weather conditions, due to the temperature inversion occurring during anticyclonic circulation [31], when pollutant concentrations increase. This study focused on the concentrations of PM 2.5 particulate matter in Krakow, the capital and largest city of the Lesser Poland Voivodeship.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of topography on the diversity of the city's thermal field in Krakow led to the development of the concept "relief-modified UHI effect" (Bokwa 2010;Bokwa et al, 2015). Bokwa et al (2018) studied the impact of fog on UHI intensity in Kraków, Poland, and found that fog can decrease the UHI effect by about 1 K under specific weather conditions. Półrolniczak et al (2017) analyzed the UHI effect in Poznań, Poland, and concluded that the UHI effect is more pronounced, particularly in the evening and nighttime.…”
Section: Introductionmentioning
confidence: 99%
“…The elevated number of cloud condensation nuclei from anthropogenic activities leads to higher probability of cloud (and fog) formation and precipitation in urban areas (Oke 1987, Bokwa et al 2018.The typical annual days of fog in Szeged is around 50-55, which is the consequence of the geographic location and the relatively high frequency of high-pressure synoptic patterns in autumn and winter months. Due to the projected effects of climate change, the frequency of high precipitation events will likely be increased in the forthcoming decades (Kis et al 2017) over the Carpathian Basin.…”
Section: Introductionmentioning
confidence: 99%